Customers Perception with Reference to Customer Relationship Management in Organized Retail in Visakhapatnam - et. al., Dr.V. Sai Prasanth, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article explains the customer perception with reference to Customer Relationship Management (CRM) in organized retail sector of Visakhapatnam city. This study was done with a sample size of600 customers to investigate their opinion about the quality of offered customer services by organized retails stores and its impact on customer satisfaction. The study is focused on services provided by organized retailer like Spencer’s, More, Reliance fresh, Big Bazaar and others in Visakhapatnam city. The findings show an indication that the customer perception depends on Positive attitude towards Customers, Flexible timings of purchase/ exchange, and Better grievance process.